(untitled) (Fiep Bulletin - online, 2015)
Introduction: The aptitude physical and functional capacity is determinative of the effect of the aging in the physical performance. Objective: To evaluate of physical aptitude and functional capacity in people with 50 years or more, practitioners of regular exercises. Methodology: 12 women with average age of 65 years practicing regular exercises of AFRID group, 12 of them did tests of the Table-1 and 9 of them did tests of the Table-2. The used instruments were tests: Arm curl, Flexibility of shoulder, Test to seat and to reach, Form of auto-evaluation of functional capacity (Rikli & Jones, 1999), Normal and maximum velocity of walking protocol by Williams & Greene, 1990; Velocity to stand up of the seated position, Velocity to stand up of the lying position, Velocity to stand up of the chair (CELAFISCS). Results: The results of the physical aptitude are in tables 1, 2 and they are presented average (x) and standard deviation(s), respectively. The evaluation of physical aptitude demonstrates that these values are equal and/or rather, when compared with the values reference standards, except in the test of Normal Velocity of Walking. In the auto-evaluation questionnaire it can be verified that 89, 5% had answered that they do exercises, i.e., they present advanced functional level.Conclusion: From theses results we can notice significant improvement in the physical aptitude and functional capacity of the aged practitioners of regular exercises.